The multifaceted roles of nucleophagy in cancer development and therapy. (1st December 2020) - Zhao, Lili; Li, Wenxi; Luo, Xu; Sheng, Surui
Abstract: Autophagy is an evolutionarily conserved process in which the cell degrades its own components and recycles the biomolecules for survival and homeostasis. It is an important cellular process to eliminate pathogens or damaged organelles. Nucleophagy, also termed as nuclear autophagy, is a more recently described subtype of autophagy, in which nuclear components, such as nuclear lamina and DNA, are to be degraded. Nucleophagy plays a double‐facet role in the development of cancer. On one hand, the clearance of damaged DNA or nuclear structures via autophagic pathway is crucial to maintain nuclear integrity and prevent tumorigenesis. On the other hand, in later stages of tumor growth, nucleophagy may facilitate cancer cell survival and metastasis in the nutrient‐depleted microenvironment. In this review, we discuss the relationship between nucleophagy and cancer along with potential intervention methods to target cancer through manipulating nucleophagy. Given the known observations about nucleophagy, it could be promising to target different nuclear components during the processes of nucleophagy, especially nuclear lamina. Further research on investigating the role of nucleophagy in oncological context could focus on dissecting its remaining molecular pathways and their connection to known tumor suppressors.